Principles of echocardiography and intracardiac echocardiography - Hutchison, Stuart J. (Principles of cardiovascular imaging., 2012)
Helps you to successfully obtain and interpret cardiac echo images. This title explains the dos and don'ts of echocardiography so that you get the best images and avoid artifacts.